Second World War Archaeology in Schools: A Backdoor to the History Curriculum - Gabriel Moshenska (Papers from the Institute of Archaeology, 2009)
The absence of a compulsory archaeological element in the English National Curriculum is a systemic weakness, and a problem for archaeological educators. However, historical or post-medieval archaeology offers the opportunity to make connections with the existing history curriculum at various stages, thereby introducing elements of archaeological methods and concepts into classrooms. In this paper I consider the potential for Second World War archaeology in or around the school building itself to involve students in archaeological fieldwork integrated into the National Curriculum, specifically history at Key Stage Two. Drawing on a case study of a school air raid shelter excavation in North London I examine the strengths and weaknesses of this model and discuss the scope for its broader application.
Keywords: Second World War; National Curriculum; historical archaeology; education; Community archaeology